P5.107 Clinical Practice Guideline For Sexually Transmitted Infections and Other Infection of the Genital Tract - Syndromic Management - 2012. (13th July 2013) - Duarte, H Gaitan; Rodriguez, A; Angel-Muller, E; Lopez-Gomez, H; Estrada, S; Cinets, A
Abstract : Objective: To develop a Clinical Practice Guidelines for the Syndromic management of Sexual Transmitted Infections and other Genital Tract Infections in patients between 14 and 75 years old using the current international standards. Methods: The Guidelines developer group (GDG) was composed taking into account a multidisciplinary team as well as user/patients´ point of view. The scope, questions and relevant outcomes were first defined and then a search of available CPGs was done looking for international and regional repositories and also in Medline and LILACS. The CPGs that accomplish the inclusion exclusion criteria were assessed using the AGREE II instrument. None of the evaluated guidelines were suitable to be adapted to the Colombian requirements. Based on this fact, a search for Systematic Reviews, RCT and observational studies was initiated in order to develop the novo CPG. Evidence tables were built and recommendations were elaborated following the GRADE approach using informal and formal consensus. Results: A new GPC for the management of the patients with cervicitis, urethritis, genital ulcer disease, pelvic inflammatory disease and vaginal discharge is presented. The CPG includes 80 recommendations for the diagnosis and treatment of the index patient and its partner and also for the pregnant women with GTI. The implementation plan is based on the administration of a single dose for each of the causal germens in each syndrome. Conclusion: A new evidence-based guideline is presented for Syndromic management of Sexual Transmitted Infections and other Genital Tract Infections which could be suitable for adaptation in settings of constrained resources. Source of funds: Ministry of Health of Colombia and COLCIENCIAS.